Non-destructive image analysis of soil surface porosity and bulk density dynamics - Pires, L.F.; Cássaro, F.A.M.; Bacchi, O.O.S.; Reichardt, K. (Radiation physics and chemistry (Oxford, England : 1993), 2011)
A gamma-ray computed tomography (CT) scanner was used to evaluate changes in the structure of clayey soil samples with surface compaction submitted to wetting and drying (W–D) cycles. The obtained results indicate that W–D cycles promoted an increasing of about 10% in soil porosity with a decreasing of about 6% in soil bulk density of this compacted region. With the use of the CT it was also possible to define the thickness of the compacted region that in our case was of about 8.19mm. This last information is very important, for instance, to estimate hydraulic parameters in infiltration models. Finally, CT analysis showed that the compacted region remained at the surface samples, even after the application of the W–D cycles. ► Gamma-ray tomography allowed non-destructive analysis of soil bulk density and porosity changes. ► Soil porosity increased about 10% with the wetting and drying cycles. ► Soil bulk density in the compacted region decreased about 6% with the wetting and drying cycles. ► Detailed bulk density and porosity analysis changes were obtained for layers of 1.17mm.